eCM 2014
DOI: 10.22203/ecm.v027a20
|View full text |Cite
|
Sign up to set email alerts
|

Submicron-scale surface architecture of tricalcium phosphate directs osteogenesis in vitro and in vivo

Abstract: A current challenge of synthetic bone graft substitute design is to induce bone formation at a similar rate to its biological resorption, matching bone's intrinsic osteoinductivity and capacity for remodelling. We hypothesise that both osteoinduction and resorption can be achieved by altering surface microstructure of beta-tricalcium phosphate (TCP). To test this, two TCP ceramics are engineered with equivalent chemistry and macrostructure but with either submicron-or micron-scale surface architecture. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 48 publications
13
90
0
Order By: Relevance
“…In support of this theory, it has been reported that osteoclastogenesis precedes osteoinduction by microstructured TCP by several weeks (Akiyama et al, 2011;Kondo et al, 2006), and osteoclast depletion limits (Ripamonti et al, 2010) or completely blocks de novo bone formation by osteoinductive CaPs (Davison et al, 2014a). Recently, we reported a clear link between TCP microstructure, osteoclastogenesis, and subsequent de novo bone formation (Davison et al, 2014a;Davison et al, 2014b). However, (pre-)osteoclast differentiation and activity is influenced by multiple substrate parameters including surface nano-/microroughness (Makihira et al, 2007;Webster et al, 2001), solubility (Benahmed et al, 1996;Yamada et al, 1997), and the accompanied release of nano-/microparticulate (Fellah et al, 2007;Velard et al, 2013), so it is currently unknown if this link also holds true for less resorbable materials like BCP or titanium.…”
Section: Nl Davison Et Al Osteoinduction and Osteoclastogenesis By Bsupporting
confidence: 67%
See 4 more Smart Citations
“…In support of this theory, it has been reported that osteoclastogenesis precedes osteoinduction by microstructured TCP by several weeks (Akiyama et al, 2011;Kondo et al, 2006), and osteoclast depletion limits (Ripamonti et al, 2010) or completely blocks de novo bone formation by osteoinductive CaPs (Davison et al, 2014a). Recently, we reported a clear link between TCP microstructure, osteoclastogenesis, and subsequent de novo bone formation (Davison et al, 2014a;Davison et al, 2014b). However, (pre-)osteoclast differentiation and activity is influenced by multiple substrate parameters including surface nano-/microroughness (Makihira et al, 2007;Webster et al, 2001), solubility (Benahmed et al, 1996;Yamada et al, 1997), and the accompanied release of nano-/microparticulate (Fellah et al, 2007;Velard et al, 2013), so it is currently unknown if this link also holds true for less resorbable materials like BCP or titanium.…”
Section: Nl Davison Et Al Osteoinduction and Osteoclastogenesis By Bsupporting
confidence: 67%
“…Crystal chemistry of the materials was analysed by X-ray diffraction (Rigaku Miniflex II) scanning the range 2θ = 25-45° (step size = 0.01°, rate = 1° min -1 ) as previously described (Davison et al, 2014b). The surface reactivity of the discs was analysed in simulated physiologic solution (SPS) (50 mM HEPES, 140 mM NaCl, and 0.4 mM NaN 3 for sterility; all from Sigma Aldrich, Saint Louis, MO, USA) at pH 3 and pH 7.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations